Tagged spectator deep-inelastic scattering off the deuteron as a tool to study neutron structure - Cosyn Wim; Sargsian Misak (EPJ Web of Conferences, 2016)
We give an overview of a model to describe deep-inelastic scattering (DIS) off the deuteron with a spectator proton, based on the virtual nucleon approximation (VNA). The model accounts for the final-state interactions (FSI) of the DIS debris with the spectator proton. Values of the rescattering cross section are obtained by fits to high-momentum spectator data. By using the so-called “pole extrapolation” method, free neutron structure functions can be obtained by extrapolating low-momentum spectator proton data to the on-shell neutron pole. We apply this method to the BONuS data set and find a surprising Bjorken x dependence, indicating a possible rise of the neutron to proton structure function ratio at high x.